The relation between social isolation and increasing suicide rates in the elderly - Heuser, Christoph; Howe, Juergen (Quality in Ageing and Older Adults, 2019)
Purpose - Suicidal attempts and thoughts are particularly relevant to the health of the elderly and can impact not only the individual, but family, friends and spouses as well. This topic is important for the gerontological research community, particularly as it relates to social isolation and the feeling of loneliness, common in this population group. The purpose of this paper is to investigate new knowledge about the relationship between an increased risk of suicide in the elderly and social isolation or loneliness.
CRIS-Team WoS Importer:2019-04-30